2014
DOI: 10.1016/j.jbiomech.2014.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in trabecular bone microarchitecture in the ovine spine and distal femur following ovariectomy

Abstract: Osteoporosis is a bone disease resulting in increased fracture risk as a result of alterations in both the quantity and quality of bone. Bone quality is a combination of metabolic and microarchitectural properties of bone that can help to explain the increased susceptibility to fracture. Translational animal models are essential to understanding the pathology and evaluating potential treatments of this disease. Large animal models, such as the ovariectomized sheep, have been used as a model for post-menopausal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…In-vitro laboratory studies of utilising CT to explore the effects of microarchitecture have been made on normal and ovariectomised animal proxies (Mittra et al, 2005, Teo et al, 2006, Kreipke et al, 2014) and these explored the relationship between microarchitecture and mechanical properties of cancellous bone as well as alterations to trabecular microarchitecture following ovariectomy. There only a few studies utilising human biopsies and these suffer from low sample numbers possibly due to the difficulty of obtaining substantial amount of human osteoporotic bone material (Zhang et al, 2010, Green et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In-vitro laboratory studies of utilising CT to explore the effects of microarchitecture have been made on normal and ovariectomised animal proxies (Mittra et al, 2005, Teo et al, 2006, Kreipke et al, 2014) and these explored the relationship between microarchitecture and mechanical properties of cancellous bone as well as alterations to trabecular microarchitecture following ovariectomy. There only a few studies utilising human biopsies and these suffer from low sample numbers possibly due to the difficulty of obtaining substantial amount of human osteoporotic bone material (Zhang et al, 2010, Green et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Minimal differences in architecture were seen in the femoral condyles in the ovariectomized sheep model (Kreipke et al, 2014). Because of this, the samples were not representative of osteoporotic human bone (Krug et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, Sigrist et al (2007) reported that in sheep, 6 months after the OVX, the markers for formation and resorption returned to baseline, indicating that the model was not appropriate for human postmenopausal osteoporosis. Kreipke et al (2014) reported that OVX induces the necessary changes in bone microarchitecture for studying osteoporosis, but after a year, the changes in architecture stabilize in ovine. Chavassieux et al (2001) reported that in goats, remodelling occurred only in the cortical bone tissue regions, which was also demonstrated by increased levels of CTx one month after OVX and OC three months after OVX.…”
Section: Osteoporosismentioning
confidence: 99%